Water Feasibility Study of Bengawan Solo River for Irrigation: The Need for Technology to Solve Rice Field Pollution in Sragen, Indonesia - Setiyo Prajoko (International Journal of Applied Biology, 2018)
The aims of this study are to determine the feasibility of Bengawan Solo River water for irrigation of rice field in Sragen, Central Java and to find solution to the problem. The data used in this study were obtained from various literatures related to the issues discussed. The collected data were then selected and analyzed with descriptive argumentative. The result indicates that the water quality of Bengawan Solo River has dropped below the water quality standard grade IV according to Government Regulation Number 82 Year 2001. The use of water from this river has caused the quality of rice to decline below the rice quality standard according to Indonesian National Standard (SNI) 01.6128-2008 due to the bioaccumulation of heavy metals on rice crops, i.e. copper (Cu), mercury (Hg), cadmium (Cd), and Chromium (Cr) exceeded the threshold. Solution proposed to overcome this problem is with counseling programs to farmers conducted by relevant agencies on the use of rice field pollution control technology by physics, chemistry, and biology.